2016
DOI: 10.1615/intjmedmushrooms.v18.i2.80
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Indian Lingzhi or Reishi Medicinal Mushroom, Ganoderma lucidum (Agaricomycetes): A UPC2-SQD-MS Approach

Abstract: Oriental medicinal mushroom Ganoderma lucidum has been widely used for the promotion of health and longevity owing to its various bioactive constituents. Therefore, comprehending metabolomics of different G. lucidum parts could be of paramount importance for investigating their pharmacological properties. Ultra-performance convergence chromatography (UPC2) along with mass spectrometry (MS) is an emerging technique that has not yet been applied for metabolite profiling of G. lucidum. This study has been underta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 0 publications
2
7
0
Order By: Relevance
“…Regarding aqueous extracts, GLMaq gave a higher percentage yield by weight (5.7%) than GLFaq (2.8%). This observation is in concurrence with previous reports where aqueous extract of G. lucidum mycelium, prepared by accelerated solvent extraction, gave better yield than G. lucidum fruiting body [13]. Between the diethyl ether fractions, GLFdee gave a fairly better yield (3.8%) than GLMdee (3.28%).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Regarding aqueous extracts, GLMaq gave a higher percentage yield by weight (5.7%) than GLFaq (2.8%). This observation is in concurrence with previous reports where aqueous extract of G. lucidum mycelium, prepared by accelerated solvent extraction, gave better yield than G. lucidum fruiting body [13]. Between the diethyl ether fractions, GLFdee gave a fairly better yield (3.8%) than GLMdee (3.28%).…”
Section: Resultssupporting
confidence: 92%
“…Though any particular trend pertaining to the antioxidant capacity of the phenolic fractions was not obtained, it was clearly observed that both the mycelium and fruiting body fractions possessed substantial antioxidant potential. Similar observations were acquired for aqueous, methanolic, and ethyl acetate fractions of G. lucidum where both mycelium as well as the fruiting body exhibited appreciable antioxidant activities [13].…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations